P133 Modelling REM-NREM activity cycling in infants. (9th November 2022) - Webb, L; Phillips, A; Roberts, J
Abstract: Sleep states in infancy differ from adult sleep states. Due to different cortical and physical manifestations, the REM and NREM equivalent sleep states in infants are often denoted as Active and Quiet sleep. Key differences in infant REM-NREM cycling include rapid cycling, and commencement of sleep in the REM state, instead of NREM. The physiological mechanisms underlying developmental changes in REM-NREM cycling in infancy are not well understood. We extended an existing, physiologically based model of sleep-wake behaviour to include a REM-on group and REM-off group, with mutual inhibition between these providing the basis for REM-NREM cycling. We model a REM pressure driving the REM-NREM cycling, similar to other proposed models and motivated by the known phenomenon of increased REM sleep following REM deprivation. We found parameter combinations that produce the REM-NREM cycling observed in infancy and early childhood. Through varying the parameters governing the dynamics of the REM pressure drive, the model is able to reproduce both newborn infant Wake-REM-NREM behaviours and the older Wake-NREM-REM pattern. Our results suggest that REM pressure clearance plays a dominant role in determining the initial sleep state, and increases in REM pressure from wake/NREM controls REM latency and duration. We have identified a plausible mechanism for the immature sleep state cycling observed in infants. In line with theories of REM sleep's purpose in cortical synaptic remodelling, a process which evolves rapidly in infancy, we found that REM pressure clearance times likely vary along early development, triggering a switch from REM-first to NREM-first sleep.